Psychological Distress in the Quarter-life Crisis: The Role of Psychological Inflexibility - Amanda Delisia; Roswiyani; Monty P. Satiadarma (Bisma The Journal of Counseling, 2023)
The developmental transition from adolescence to adulthood involves many developmental demands, so many individuals experience the Quarter-life crisis phenomenon. Individuals experiencing this crisis may experience increased psychological distress. Psychological distress can disrupt life, so it needs to be treated seriously. This research aims to determine the relationship between psychological inflexibility and psychological distress in individuals experiencing a quarter-life crisis. This research uses a quantitative approach with a correlational design. Participants consisted of 107 individuals aged 20-29 who were experiencing a quarter-life crisis and were selected using purposive sampling. Research measurements were conducted using The Hopkins Symptoms Checklist-25 (α = 0.894) and Acceptance and Action Questionnaire-II (α = 0.822). Data analysis was carried out using simple regression test statistical techniques. The results of the analysis show that high psychological inflexibility can predict higher psychological distress (R2 = 0.249; p < 0.001). Psychological inflexibility contributed 24.9% to psychological distress. It can be concluded that individuals in QLC who have rigid psychological reaction patterns can experience more severe symptoms of anxiety and depression. Research findings are helpful for practitioners to target interventions that focus on reducing psychological inflexibility so that psychological distress can be reduced.